Formation of redox-active self-assembled polyelectrolyte-surfactant complexes integrating glucose oxidase on electrodes: Influence of the self-assembly solvent on the signal generation - Cortez, María Lorena (2015)
In this work the effects of the self-assembly solvent on the structure and electrochemical behavior of redox-active polyelectrolyte-surfactant complexes cast on electrode supports from aqueous and DMF solutions are presented. The complex studied is formed by complexation of osmium complex-modified polyallylamine (OsPA) with dodecyl sulfate (DS) surfactants. The structure of the films was characterized by GISAXS, showing that films present a lamellar mesostructure. However, when they are exposed to humid environments, films cast from aqueous solutions (OsPA-DSaq) undergo a structural transition that ultimately leads to the disappearance of the mesostructural order. On the other hand, OsPA-DS films cast from DMF solutions (OsPA-DSorg) revealed no significant changes upon exposure to humid environments. Both types of films were exposed to glucose oxidase (GOx), showing similar adsorption characteristics. Notwithstanding these similarities in GOx and content, OsPA-DSaq films revealed a more sensitive bioelectrocatalytical response to glucose as compared to OsPA-DSorg films.